2021
DOI: 10.1002/jmd2.12253
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of eating and psychosocial problems in patients with hepatic glycogen storage diseases and idiopathic ketotic hypoglycemia: Towards a standard set of patient‐reported outcome measures

Abstract: There is a paucity in literature on eating and psychosocial problems in patients with hepatic glycogen storage disease (GSD) and idiopathic ketotic hypoglycemia (IKH), problems that can greatly affect quality of life. This is a monocentre, retrospective, observational mixed method study of patients with hepatic GSD or IKH treated at the Beatrix Children's Hospital Groningen, who had been referred to SeysCentra, a specialist centre for the treatment of eating problems. Additionally, a systematic literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
(82 reference statements)
1
14
0
Order By: Relevance
“…GSD associated feeding difficulties are being increasingly recognized. 38 , 39 , 40 Oral aversion was reported in 47% of our patients, which is similar to findings from Martinez et al who found that 30% of patients with GSD had oral aversion, compared to of 0.25% in the general population. 39 , 41 All patients who started cornstarch within 2 months of birth, who had been diagnosed by cord blood developed oral aversion.…”
Section: Discussionsupporting
confidence: 91%
“…GSD associated feeding difficulties are being increasingly recognized. 38 , 39 , 40 Oral aversion was reported in 47% of our patients, which is similar to findings from Martinez et al who found that 30% of patients with GSD had oral aversion, compared to of 0.25% in the general population. 39 , 41 All patients who started cornstarch within 2 months of birth, who had been diagnosed by cord blood developed oral aversion.…”
Section: Discussionsupporting
confidence: 91%
“…One study took place in the Middle East (Iron‐Segev et al., 2022) and six in East Asian countries: four in Japan (Dinkler et al., 2022a, 2022b; Seike et al., 2016a, 2016b), one in Taiwan (Chen et al., 2020) and one in Singapore (Wong et al., 2022). The majority ( n = 21) of studies focussed on clinical populations (Bertrand et al., 2021; Cooney et al., 2018; Eddy et al., 2015; Farag et al., 2022; Fisher et al., 2014, 2015; Forman et al., 2014; Goldberg et al., 2020; Katzman et al., 2021; Koomar et al., 2021; Krom et al., 2019; Murray et al., 2022; Nicely et al., 2014; Norris et al., 2014; Nygren et al., 2021; Ornstein et al., 2013; Pinhas et al., 2017; Schöffel et al., 2021; Venema et al., 2022; Williams et al., 2015; Wong et al., 2022) with many drawing on samples from adolescent eating disorders services or feeding clinics ( n = 11) (Cooney et al., 2018; Farag et al., 2022; Fisher et al., 2014, 2015; Forman et al., 2014; Krom et al., 2019; Nicely et al., 2014; Norris et al., 2014; Ornstein et al., 2013; Williams et al., 2015; Wong et al., 2022) and utilising retrospective chart review methodology ( n = 13) (Cooney et al., 2018; Eddy et al., 2015; Fisher et al., 2014; Krom et al., 2019; Murray et al., 2022; Nicely et al., 2014; Norris et al., 2014; Nygren et al., 2021; Ornstein et al., 2013; Schöffel et al., 2021; Venema et al., 2022; Williams et al., 2015; Wong et al., 2022). All studies were cross‐sectional in design and ARFID diagnosis used the DSM‐5 or instrum...…”
Section: Resultsmentioning
confidence: 99%
“…Eating disorders in children and adults with GSDIa [64,76] and the psychosocial impact of the disease in adults [77] have been reviewed. Additionally, parents/caregivers of children with GSDIa experience greater stress and distress versus parents/caregivers of children without a chronic disease [41].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Individuals may experience fear, anxiety and stress associated with missed doses of UCCS and the potential consequences, as well as concerns regarding physical appearance (e.g., due to growth retardation, weight gain or body shape) [64,79]. Weight gain has been highlighted by patients as another of the most frustrating aspects of the disease [62], and patients are at risk of developing eating disorders, such as avoidant/restrictive food intake disorder [64,76]. A large proportion of daily calories are obtained from UCCS, which may affect appetite, and chronic use of continuous overnight enteral feeding has been associated with eating disorders and anorexia.…”
Section: Quality Of Lifementioning
confidence: 99%